Pengaruh Kecepatan, Fleksibilitas, dan Kekuatan Ledakan Otot Kaki terhadap Kemampuan Tendangan Bulan Sabit pada Atlet Pencak Silat Muda - Irfan Fuady; Hendri Neldi; Vega Soniawan; Alnedral Alnedral (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Crescent kick performance is essential in pencak silat, yet limited evidence exists on how speed, flexibility, and leg muscle explosive power interact to determine this skill among young athletes, particularly given the suboptimal achievement in Kabupaten Pelalawan at the POPDA competition. This research examines the direct and indirect influences of these three biomotor components on crescent kick proficiency among young athletes aged 14-17 years in Pangkalan Kerinci District. Materials and methods. A quantitative approach with path analysis design was employed. The study population comprised 44 young pencak silat athletes aged 14 - 17 years in Pangkalan Kerinci District using saturated sampling. Data collection utilized a 30 meter sprint test, front split test, standing long jump test, and 10 second repetitive kicking test. Data analysis used Jamovi version 2.6.44. Results. Speed directly influenced crescent kick ability (0.657; p<0.001). Flexibility also demonstrated a direct effect (0.281; p<0.001). Leg muscle explosive power showed a direct effect (0.332; p<0.001). Speed exhibited an indirect effect through leg muscle explosive power (31.1%; p<0.001), while flexibility demonstrated a stronger indirect effect (63.4%; p<0.001). All three variables simultaneously influenced crescent kick ability (F=320; p<0.001; R²=0.960). The main strength is the use of path analysis, while the limitation is the cross-sectional design and 4% unexplained variance. Conclusions. Speed, flexibility, and leg muscle explosive power significantly affect crescent kick ability. Leg muscle explosive power functions as a partial mediator, particularly dominant in the flexibility crescent kick relationship. The theoretical implication enriches sports science knowledge regarding mediation mechanisms. Practically, training programs should integrate these three components systematically. Future experimental research is recommended to test training program effectiveness and consider additional factors such as coordination, balance, and psychological aspects.